Management practices and productivity: Does employee representation play a moderating role? - Uwe Jirjahn; Marie-Christine Laible; Jens Mohrenweiser (Human Resource Management Journal, 2023)
Bloom and Van Reenen (2007) have suggested an index of best management practices capturing three broad areas: monitoring, targets and incentives. However, it is an open question whether the functioning of these practices depends on contextual factors. From a theoretical viewpoint, the management practices involve both productive and dysfunctional effects. We hypothesize that the relative strength of these effects depends on the industrial relations climate. Works councils help management practices live up to their potential by building long-term employer-employee cooperation. Our empirical analysis uses panel data from the German Management and Organizational Practices survey to examine this hypothesis. Applying a reformulated version of the Mundlak estimator, we disentangle short-term and sustaining productivity effects of the management practices. Our results show that the incidence of a works council specifically strengthens the sustaining productivity effect of the practices.
Keywords: 650; incentives; monitoring; productivity; targets; works council